Penundaan Pembayaran Angsuran Kepemilikan Rumah: Telaah Empiris Sanksi Nasabah BSI Menurut Fatwa DSN-MUI No. 17/DSNMUI/IX/2000 - Maya Kristia Ningsih; Abdul Wahab Abd Muhaimin; Umi Khusnul Khotimah (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2023)
If customers make the delay in payment of home ownership financing installment, Bank Syariah Indonesia (BSI) will impose punishments in the form of warning letters for them. This research discusses the application of punishment (ta'zir), the accordance of sanctions (ta'zir) with Fatwa DSN-MUI No.17/IX/2000 concerning capable customers who delay payments, and the purpose of applying sanctions (ta'zir) for customers of BSI. The type of research used is qualitative research, with primary data obtained from interviews. The research object is BSI located in Central Jakarta. The empirical juridical approach is used to elaborate the research data. The results of this study reveal that the punishment (ta'zir) of BSI has been guided by the accordance of “Fatwa DSN-MUI NO:17/DSNMUI/IX/2000 Tentang Sanksi Nasabah Mampu Yang Menunda-nunda Pembayaran Angsuran Pembiayaan Kepemilikan Rumah Menggunakan Akad Murabahah”. In other words, the provisions of Fatwa DSN-MUI No. 17/DSN-MUI/IX/2000 concerning sanctions for capable customers who delay payments are in accordance with the practices applied by BSI as a bank under Islamic principle. in Indonesia. Punishments are imposed on customers who are capable but deliberately delay payments. In contrast, sanctions (ta`zīr) do not apply to customers who do not pay their installments due to force majeure or experience unwanted losses involving human factors.